Framing Pemberitaan Mengenai Pernikahan Beda Agama Disahkan Pengadilan Negeri Surabaya - Hanafi, Hanafi; Aldiansyah, Rizky; Reza, Faisal; Ilham, Yanuar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The interfaith marriage passed by the Surabaya District Court is an event that needs to be reviewed by government agencies, because it is an opening tap for people to perform marriages in terms of legal loopholes that apply for applying for interfaith marriages. In this case, the Surabaya District Court has contradicted the first precept, namely the Almighty Godhead and Law Number 1 of 1974 concerning Marriage. The MUI has confirmed that interfaith marriage cannot be carried out in the State of Indonesia and the MUI fatwa declares it haram related to interfaith marriages passed by the Surabaya District Court. This study used robert N. Entman's framing model analysis to determine the framing carried out by the two media, namely Detik.com and Republika.co.id in reporting on interfaith marriages passed by the Surabaya District Court. The purpose of this study is to find out how to Detik.com and Republika.co.id in describing the four elements of Robert N. Entman's analysis, namely define problems( definition of problems), diagnose causes (causes of problems), make moral judgement (make moral decisions), and treatment recommendations (problem solving) in the news of interfaith marriage was ratified by the Surabaya District Court edition 20 – 28 July 2022. This research uses framing theory. This research method refers to the paradigm of constructivism. The design of this study used a framing analysis study. In this study, the data collection technique carried out by the author used triangulation of data sources as a technique to check the validity of the data. Based on the results of the study, it can be concluded that Detik.com and Republika.co.id have different views in forming a news construction. This can be seen from the four elements of Robert N. Entman's framing analysis in the news of interfaith marriages passed by the Surabaya District Court..